Pelatihan Peningkatan Kesadaran Anti-Perundungan dan Pencegahan Perilaku Perundungan di SMP Gembala Baik Pontianak - Tetty Simbolon; Hemma Gregorius Tinenti; Martinus Martinus; Jimiana Bunga (Lembaga Pengembangan Kinerja Dosen, 2026)
The lack of awareness regarding the emotional impact of bullying remains a persistent issue in schools. It hinders students’ ability to build self-confidence, form healthy social relationships, and reach their full academic potential. In response to this concern, an anti-bullying training program was implemented at a junior high school (SMP Gembala Baik Pontianak). The program aimed to enhance students’ understanding of different forms of bullying and their consequences, while also promoting active participation in fostering a safe and supportive school environment. The training employed a multi-phase approach: material preparation, interactive presentations, group discussions, empathy-building exercises, and evaluation through questionnaires and behavioural observation. The results were notable: 98.91% of participants demonstrated improved understanding of bullying and its serious effects, while 73.11% reported increased confidence in reporting bullying incidents. Furthermore, 95.69% of students acknowledged that the training helped them appreciate the importance of embracing diversity and creating a safe environment. Additionally, 83.87% felt more motivated to show empathy toward their peers. These findings suggest that effective bullying prevention extends beyond information delivery—it must also engage students emotionally and instill a sense of personal responsibility. Similar programs are recommended to be held regularly with updated and contextually relevant materials.